Formulation and Physical Stability Test of Lotion O/W Potato Starch (Solanum tuberosum L.) and the Activities as Sunscreen - Abdul Karim Zulkarnain; Luky Oktaviasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Potato starch has an opaque characteristic that cannot be penetrated by light but can reflect light, therefore it is useful to prevent the penetration of ultraviolet radiation on the skin. This study aims to obtain a sunscreen product from natural material namely potato starch in lotion form. The experiment uses potato starch made into lotion in oil in water form with the concentrations of potato starch 10; 12.5; 15; 17.5 and 20% w/w. Physical evaluations of lotion formulation were done during storage with physical quality controlling, homogeneity, pH, viscosity, dispersive test, adhesion test, and product stability with a freeze-thaw cycle. Sunscreen activity is done by finding the value of sun protection factor (SPF) of potato starch lotion which determined by in vivo method using albino rabbit that induction by 8-MOP or methoxsalen previously, and irradiated by UV lamp. The 15% concentration variation of potato starch provides the most stable lotion based on the organoleptic parameter, homogeneity, pH, viscosity, dispersive test, adhesion test, and product stability accelerated. The increasing of potato starch concentration gives effect to the physical stability of the lotion during the storage time. Oil in water potato starch lotion with 15% has activity as a sunscreen with SPF value 15.